Unlocking potential social value creation to improve digital startup performance: The role of government institutional support and social entrepreneurship - Septian Wahyudi; I. Made Sukresna; Rintar Simatupang (Scientific Papers of the University of Pardubice, Series D: Faculty of Economics and Administration, 2022)
The main goal of social entrepreneurship is to achieve organisational performance while facing various challenges, including a lack of financial support and difficulty harmonizing commercial activities with social missions. The authors suggest that government institutional support can revitalize social entrepreneurship through financial support and various policy measures. In addition, social entrepreneurship can increase the creation of social change to meet their social needs, known as social value creation. Hence, this study proposes institutional factors and social entrepreneurship as predictors of social value creation. Social value creation mediates the relationship between social entrepreneurship and organisational performance grounded on innovation theory. The study applies structural equation modeling with AMOS-24 software to test the research hypotheses with 249 Indonesian digital startups with a social impact as a sample. The results find that government institutional support can increase social entrepreneurship and enhance social value creation. As hypothesized, social value creation is a mediator in improving organisational performance. This study contributes to a comprehensive understanding of government institutional support, social entrepreneurship, social value creation, and organisational performance.
Keywords: L26; M13; 330; Government institutional support; Social entrepreneurship; Social value creation; Innovation theory; Digital start-up